2020
DOI: 10.3390/molecules25153355
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and the PI3K Inhibitor: LY294002 Synergistically Induce Apoptosis and Cell Cycle Arrest in Breast Cancer MCF-7 Cells

Abstract: Breast cancer is considered as one of the most aggressive types of cancer. Acquired therapeutic resistance is the major cause of chemotherapy failure in breast cancer patients. To overcome this resistance and to improve the efficacy of treatment, drug combination is employed as a promising approach for this purpose. The synergistic cytotoxic, apoptosis inducing, and cell cycle effects of the combination of LY294002 (LY), a phosphatidylinositide-3-kinase (PI3K) inhibitor, with the traditional cytotoxic anti-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Further analysis revealed downregulation of pAkt and cyclin D1 after combined treatment. On the other hand, downregulation of anti-apoptotic genes, including Bcl-2 and survivin, was detected after LY294002 and tamoxifen co-treatment in MCF-7 cells [ 98 ]. In a recent study, tamoxifen-xanthene hybrid induced mitochondria-mediated apoptosis due to activation of PARP cleavage, upregulation of Bim gene expression and increase in Bax/Bcl2 ratio in MCF-7 cells [ 99 ].…”
Section: Mechanisms Of Tamoxifen-induced Apoptosismentioning
confidence: 99%
“…Further analysis revealed downregulation of pAkt and cyclin D1 after combined treatment. On the other hand, downregulation of anti-apoptotic genes, including Bcl-2 and survivin, was detected after LY294002 and tamoxifen co-treatment in MCF-7 cells [ 98 ]. In a recent study, tamoxifen-xanthene hybrid induced mitochondria-mediated apoptosis due to activation of PARP cleavage, upregulation of Bim gene expression and increase in Bax/Bcl2 ratio in MCF-7 cells [ 99 ].…”
Section: Mechanisms Of Tamoxifen-induced Apoptosismentioning
confidence: 99%
“…However, a large number of clinical trials in which targeted therapy was tested have indicated that monotherapy is not sufficient and has limited efficacy. Therefore, combination therapy has greater potential [ 2 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR (Applied Biosystems 7500 Fast Real Time PCR System, Waltham, MA, USA) was applied to quantify the gene expression of P-gp and Hsp90 in MCF7/ADR cells [ 63 ]. Briefly, MCF7/ADR cells (2 × 10 6 cells/well) were cultivated in 6-well plates for 72 h, then cells were treated with vehicle control (0.00 µM), doxorubicin (1 µM), HAA 2021 (0.25 µM) or their combination.…”
Section: Methodsmentioning
confidence: 99%